Rancang Bangun Aplikasi Penjualan Pada PT Panca Patriot Prima - Baya, Novi Riyanto Dwi Putra; Wulandari, Sri Hariani Eko; Sudarmaningtyas, Pantja Wati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
: PT Panca Patriot Prima is a company engaged in broiler chicken farms. For the sales process broiler breeder companies have many partners. Based on the analysis in the can at PT Panca Patriot Prima has constraints in determining the amount of the sales activities of broiler chickens. During the determination of the amount of sales of broilers not be seen from the number of broiler chicken sales turnover by the broker and also do not consider the amount of remaining debt broker.Companies should be in the process of determining the number of broiler chicken sales are centered on brokers. Companies in selling broiler provide a platform for a number of broiler chicken sales to brokers based on the amount of turnover and the number of remaining debt broker.Based on the above, the authors provide a solution to solve the problem of the sale of chicken broileryaitu build sales application that was able to determine the number of broiler chicken sales to the broker.Results from making this application is that it can help companies to determine the amount of sales of broilers to brokerberdasarkan amount of the turnover and the number of remaining debt can brokerserta address issues regarding the payment